2005
DOI: 10.1063/1.1905794
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric magnetization reversal in exchange-biased NiFe∕CoO submicron-sized structures

Abstract: Exchange coupling in patterned exchange-biased NiFe/ CoO squares with different sizes has been studied. Arrays of square dots with the lateral size varying between 300 and 900 nm and a fixed interdot distance of 800 nm were prepared by sputtering followed by in situ oxidation. Exchange bias in the initial and trained loops was studied as a function of the size, temperature, and cooling field. A decrease in the exchange bias shift was observed with a decreasing size, which might be due to the magnetostatic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…It has been shown that for nanostructures, the AFM layer is weakly pinned to the FM layer as compared to the continuous film due to thermal activation effects. 19,21,[49][50][51] This results in lower blocking temperatures for nanostructures when compared to continuous films. For instance, in NiFe/ IrMn systems, the blocking temperature in nanodots is observed to be lower as compared to the continuous film.…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that for nanostructures, the AFM layer is weakly pinned to the FM layer as compared to the continuous film due to thermal activation effects. 19,21,[49][50][51] This results in lower blocking temperatures for nanostructures when compared to continuous films. For instance, in NiFe/ IrMn systems, the blocking temperature in nanodots is observed to be lower as compared to the continuous film.…”
Section: ͑1͒mentioning
confidence: 99%
“…This "freezing" of AFM spins induces unidirectional anisotropy in the system which can be tailored by controlling several factors such as the field cooling strength, thicknesses of AFM or FM layers, and by structural confinement of AFM domain sizes. Although the microscopic origin of exchange bias effect is still not elucidated completely despite exhaustive experimental 4,6-8 and theoretical studies, [9][10][11][12][13][14][15] there have been few observations on its characteristic features: ͑i͒ the shift in the hysteresis loop along its field axis ͑H EB ͒ and increase in coercivity ͑H C ͒ as the system is cooled in an applied magnetic field below the blocking temperature of the AFM layer, [16][17][18] ͑ii͒ different magnetization reversals for the ascending and descending parts of the hysteresis loop, [19][20][21] and ͑iii͒ the time relation effects of H EB and H C indicate that a stable magnetic state is reached only at very low temperatures. 22 One of the important factors in explaining the origin of exchange bias is the irreversible nature of the AFM interface magnetization arising from volume domains stabilized by defects in the AFM layer.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetry of the magnetization reversal curves at the patterned film (see the arrows on the figures) varies monotonically with decreasing size of the magnetic dots. A small shoulder appears for the first time in the upper magnetization curve in figure 2(a) and becomes more pronounced as the size of the dots decreases, leading almost to the 'disappearance' of the exchange bias (EB) effect for the sample with the smallest dots [6,7] in figure 2(d). Presumably, this odd behaviour caused by incomplete biasing due to a competition between magnetostatic inter-dot interactions and exchange anisotropy energy at the FM/AFM interface.…”
Section: The Size Dependencementioning
confidence: 99%
“…Both parameters can be tailored by exchange coupling the ferromagnetic ͑F͒ nanoelement to an extended antiferromagnetic ͑AF͒ substrate. These issues have recently been investigated in experimental studies of arrays of interface biased ferromagnetic dots, Fe/ FeF 2 , [16][17][18][19] Ni/NiO, 21 NiFe/CoO, 22,23 NiFe/IrMn, 24 and Co/CoO. 25 Early reports have shown that the exchange bias of Fe/ FeF 2 patterned bilayers can be tuned by their lateral dimensions.…”
Section: Introductionmentioning
confidence: 99%